WIND ENERGY EVALUATION AND TURBINE IDENTIFICATION FOR POWER GENERATION IN SOME SELECTED AREAS IN NIGERIA - MUSEDIQ ADEDOYIN SULAIMAN; IGNATIUS KEMA OKAKWU; AKINTUNDE SAMSON ALAYANDE; OLAKUNLE ELIJAH OLABODE; AUGUSTUS EHIREMEN IBHAZE (Journal of Engineering Studies and Research)
In this paper, the wind power potentials as well as wind speed characteristics of four selected locations in the North-Central (Ilorin and Makurdi) and North-East (Gombe and Maiduguri) parts of Nigeria are investigated. The data used are obtained from Nigeria Meteorological Agency (NIMET) between the durations of 11 and 54 years, measured at an anemometer height of 10m. The analysis of the data is carried out using a two-parameter Weibull Distribution Function (WDF). The most probable wind-speed and the wind-speed carrying the maximum energy were also evaluated. The capacity factor estimation is then used to identify the most suitable turbine for the sites. The results obtained show a monthly mean wind-speed of 4.50 m/s, 3.72 m/s, 4.77 m/s and 5.34 m/s for Ilorin, Gombe, Makurdi and Maiduguri respectively, while the wind-power densities were 67.74 W/m2, 40.87 W/m2, 79.52 W/m2 and 107.49 W/m2 respectively for the same sites.